Non-price competitiveness of exports from emerging countries - Konstantins Benkovskis; Julia Wörz (European Central Bank (ECB), 2013)
Building on the methodology pioneered by Feenstra (1994) and Broda and Weinstein (2006), we construct an export price index that adjusts for changes in the set of competitors (variety) and changes in non-price factors (quality in a broad sense) for nine emerging economies (Argentina, Brazil, Chile, China, India, Indonesia, Mexico, Russia and Turkey). The highly disaggregated dataset covers the period 1996?2011 and is based on the standardised 6-digit Harmonized System (HS). Our method highlights notable differences in non-price competitiveness across markets. China shows a huge gain in international competitiveness due to non-price factors. Similarly, Brazil, Chile, India and Turkey show discernible improvements in their competitive position when accounting for non-price factors. Oil exports account for strong improvement in Russia's non-price competitiveness, as well as the modest losses of competitiveness for Argentina and Indonesia. Mexico's competitiveness deteriorates prior to 2006 and improves afterwards.
Keywords: C43; F12; F14; L15; 330; emerging countries; non-price competitiveness; quality; relative export price